Life history evolution, species differences, and phenotypic plasticity in hemiparasitic eyebrights (Euphrasia). Issue 3 (4th March 2020) - Brown, Max R.; Frachon, Natacha; Wong, Edgar L. Y.; Metherell, Chris; Twyford, Alex D.
Abstract : Premise: Species delimitation in parasitic organisms is challenging because traits used to identify species are often plastic and vary depending on the host. Here, we use species from a recent radiation of generalist hemiparasitic Euphrasia to investigate trait variation and trait plasticity. We tested whether Euphrasia species show reliable trait differences, investigated whether these differences correspond to life history trade‐offs between growth and reproduction, and quantified plasticity in response to host species. Methods: Common garden experiments were used to evaluate trait differences between 11 Euphrasia taxa grown on a common host, document phenotypic plasticity when a single Euphrasia species is grown on eight different hosts, and relate observations to trait differences recorded in the wild. Results: Euphrasia exhibited variation in life history strategies; some individuals transitioned rapidly to flowering at the expense of early season growth, while others invested in vegetative growth and delayed flowering. Life history differences were present between some species, though many related taxa lacked clear trait differences. Species differences were further blurred by phenotypic plasticity—many traits were plastic and changed with host type or between environments. Conclusions: Phenotypic plasticity in response to host and environment confounds species delimitation in Euphrasia . When grown in a common garden environment, some morphologically distinct taxa can be identified, though others represent morphologically similar shallow segregates. Trait differences present between some species and populations demonstrate the rapid evolution of distinct life history strategies in response to local ecological conditions.